Expert and Novice Performers Respond Differently to Attentional Focus Cues for Speed Jump Roping - Couvillion, Kaylee F.; Fairbrother, Jeffrey T. (Frontiers in Psychology, 2018)
The use of focus cues directing attention to an external focus has been shown to facilitate motor performance for a variety of sport and other motor skills. Results of attentional focus cue manipulations have been mixed, however, for expert performers, and other research has demonstrated that experts report using complex attentional focus strategies. Additionally, little is currently known about how focus cues affect the performance of complex continuous whole-body coordination tasks involving object manipulation such as jump roping. The purpose of this study was to examine the effects of attentional focus cues on single-rope speed jumping by experts and novices. The cues directed attention toward the upper (UP) or lower (LB) body and either internally (IN) or externally (EX). Participants (N = 30) completed bouts of speed jumping under control (CON) and experimental conditions (UPIN, UPEX, LBIN, LBEX). Jumps and Errors were recorded for each trial. Jumps were analyzed using a 2 (group: expert v. novice) × 5 (focus condition) ANOVA with repeated measures on the last factor. Errors were analyzed using a 2 (group) × 4 (focus condition) Chi Square procedure. Compared to CON, number of jumps was significantly smaller under UPIN, UPEX, and LBIN for experts (all p < .02) and under LBEX for novices (p < .001). In addition, number of jumps was significantly smaller under UPEX than LBEX (p = .049) for experts. The Chi Square analysis was significant (p < .001). Experts committed more errors under UPEX compared to CON. Errors were similar in the other conditions. Novices committed more errors under LBIN and LBEX and fewer under UPIN and UPEX compared to CON. The study provided evidence that directing attention to control of the body or the controlled object (rope) disrupted performance for experts. For novices, performance was facilitated by directing attention to the hands or the object, but was disrupted by directing attention to a lower-body outcome (foot sounds). These findings may reflect differences in mastery of whole-body coordination and are partially consistent with the Constrained Action Hypothesis despite not supporting specific predictions related to the benefit of external focus cues.